A capture-gated fast neutron detection method*Supported by National Natural Science Foundation of China (11175098, 11375095). (July 2016) - Liu 刘, Yi 毅; Yang 杨, Yi-Gang 祎罡; Tai 邰, Yang 杨; Zhang 张, Zhi 智
Abstract: To address the problem of the shortage of neutron detectors used in radiation portal monitors (RPMs), caused by the 3 He supply crisis, research on a cadmium-based capture-gated fast neutron detector is presented in this paper. The detector is composed of many 1 cm × 1 cm × 20 cm plastic scintillator cuboids covered by 0.1 mm thick film of cadmium. The detector uses cadmium to absorb thermal neutrons and produce capture γ-rays to indicate the detection of neutrons, and uses plastic scintillator to moderate neutrons and register γ-rays. This design removes the volume competing relationship in traditional 3 He counter-based fast neutron detectors, which hinders enhancement of the neutron detection efficiency. Detection efficiency of 21.66% ± 1.22% has been achieved with a 40.4 cm × 40.4 cm × 20 cm overall detector volume. This detector can measure both neutrons and γ-rays simultaneously. A small detector (20.2 cm × 20.2 cm × 20 cm) demonstrated a 3.3 % false alarm rate for a 252 Cf source with a neutron yield of 1841 n/s from 50 cm away within 15 s measurement time. It also demonstrated a very low (<0.06%) false alarm rate for a 3.21×10 5 Bq 137 Cs source. This detector offers a potential single-detector replacement for both neutron and the γ-ray detectors in RPM systems.